Keanekaragaman Vegetasi Riparian Sungai Tabir Desa Sungai Tabir Kecamatan Tabir Barat - Pitri Handayani (Pendidikan Biologi STKIP YPM Bangko, 2018)
Riparian vegetation plays an important role in maintaining the productivity of river fisheries. In addition, riparian vegetation also plays a role in controlling the entry of nutrients and toxic materials that enter the waters and store ground water. This research was conducted to find out how the level of vegetation diversity Riparian River Tabir. The method used in the analysis of vegetation is the method of line in print. The analysis of vegetation is done at the tree level. Sample plots made on the left and right side of the river are 6 transects and each transect is 3 plots / plot so that the total plot is 18 plot / plot. Data analysis includes calculation of Important Value (NP) and Type Diversity (H ') from Shannon-Wiener. The results obtained for tree level are 12 species from 9 families. The highest INP is Ficus racemosa type with INP 48.3 and H '0.29. For pole level trees, 20 species of plants are found in 14 families. The highest INP and H values were Hevea brasiliensis with INP 27 and H '0.22. For the tree level category, 14 tree species were found in 9 families. The highest INP and H values were found in Clinemia hirta INP 29.80 H '0.28. The diversity of riparian vegetation of the Tabir River is moderate for tree, pole and stake.